Board independence, internal information environment and voluntary disclosure of auditors' reports on internal controls - Ye Sun; Yang Yi; Bin Lin (China Journal of Accounting Research, 2012)
When there is high information asymmetry between directors and managers, independent directors do not have enough information to perform their functions. Only when faced with a good internal information environment can such directors acquire enough information to provide advice and monitor managers, and only under these conditions can increasing their proportion on the board effectively reduce agency problems, such as driving managers to disclose information to investors. Using a sample of Chinese listed firms that voluntarily disclose their auditors' reports on internal controls from 2007 to 2009, this study explores how the information acquisition costs of independent directors affect their monitoring effectiveness by investigating the disclosure decisions of their internal control audits. We find that when the information asymmetry between insiders and outside directors is low and the proportion of independent directors on a board is high, a firm is more likely to voluntarily disclose its internal control audit report.
Keywords: G30; K22; M41; D23; 650; Voluntary disclosure; Auditors' reports on internal controls; Board independence; Internal information environment